PEMBERDAYAAN MASYARAKAT MELAUI PROGRAM KECAKAPAN HIDUP WIRAUSAHA KULINER DI PKBM UMMATAN WASATHON KECAMATAN KASEMEN KOTA SERANG - Permana, Gilang; Fauzi , Ahmad; Ganiadi, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the community empowerment process through the Culinary Entrepreneurship Life Skills Program at PKBM Ummatan Wasathon in Kasemen District, Serang City. The program was established to address unemployment and the skills gap between the community and labor market demands by equipping learners with practical culinary entrepreneurship skills, thereby fostering economic self-reliance. A qualitative approach with a descriptive method was employed—utilizing observation, interviews, and documentation to outline the empowerment stages undertaken. The findings reveal that the empowerment process unfolded in seven stages: preparation, assessment, alternative planning, action plan formulation, implementation, evaluation, and termination. During the preparation stage, administrators formed a committee, selected facilitators, and established a partnership with the Bakti Mulia Sejahtera Producer Cooperative. The assessment stage involved psychological testing to map participants' interests and aptitudes, although challenges arose regarding participants' lack of interest in entrepreneurship. Program implementation took place twice weekly per batch but faced obstacles such as limited practical facilities and diverse participant knowledge backgrounds. Evaluations were conducted periodically to monitor the development of the learners' attitudes, knowledge, and skills. Overall, the program is considered effective in equipping learners with skills applicable to competing in the labor market or independently launching culinary businesses.